Transcutaneous vagal nerve simulation to reduce a systemic inflammatory response syndrome and the associated intestinal failure: study protocol of a prospective, two-armed, sham-controlled, double-blinded trial in healthy subjects (the NeuroSIRS-Study) - van Beekum, Cornelius J.; von Websky, Martin W.; Willis, Maria A.; Panknin, Christina; Coenen, Martin; Fimmers, Rolf; Kalff, Jörg C.; Wehner, Sven; Vilz, Tim O. (International journal of colorectal disease, 2022)
Purpose Surgery initiates pro-inflammatory mediator cascades leading to a variably pronounced sterile inflammation (SIRS). SIRS is associated with intestinal paralysis and breakdown of intestinal barrier and might result in abdominal sepsis. Technological progress led to the development of a neurostimulator for transcutaneous auricular vagal nerve stimulation (taVNS), which is associated with a decline in inflammatory parameters and peristalsis improvement in rodents and healthy subjects via activation of the cholinergic anti-inflammatory pathway. Therefore, taVNS might be a strategy for SIRS prophylaxis. Methods The NeuroSIRS-Study is a prospective, randomized two-armed, sham-controlled, double-blind clinical trial. The study is registered at DRKS00016892 (09.07.2020). A controlled endotoxemia is used as a SIRS-mimicking model. 2 ng/kg bodyweight lipopolysaccharide (LPS) will be administered after taVNS or sham stimulation. The primary objective is a reduction of clinical symptoms of SIRS after taVNS compared to sham stimulation. Effects of taVNS on release of inflammatory cytokines, intestinal function, and vital parameters will be analyzed. Discussion TaVNS is well-tolerated, with little to no side effects. Despite not fully mimicking postoperative inflammation, LPS challenge is the most used experimental tool to imitate SIRS and offers standardization and reproducibility. The restriction to healthy male volunteers exerts a certain bias limiting generalizability to the surgical population. Still, this pilot study aims to give first insights into taVNS as a prophylactic treatment in postoperative inflammation to pave the way for further clinical trials in patients at risk for SIRS. This would have major implications for future therapeutic approaches.